Comparison of Postoperative Pain Scores in Laparoscopic Cholecystectomy with Infiltration of Intraperitoneal Bupivacaine and Bupivacaine Plus Hydrocortisone - Toor, Sana Zahid; Khalid, Fizzah; Khan, Waseem Ahmed; Niaz, Muhammad Muttahhar Asim; Khurshid, Hira; Gull , Mehreen (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare postoperative pain scores in patients who underwent laparoscopic cholecystectomy (LC) with infiltration of intraperitoneal Bupivacaine vs Bupivacaine plus Hydrocortisone.Study Design: Quasi-experimental study.Place And Duration Of Study: Department of General Surgery, Pak Emirates Military Hospital Rawalpindi, Pakistan from Nov 2024 to Jun 2025.Methodology: Ninety (n=90) patients underwent LC under general anesthesia. Participants were segregated into two groups. In Group-A, intraperitoneal instillation of Bupivacaine was done and in Group-B, intraperitoneal instillation of Bupivacaine plus Hydrocortisone was done. After the surgery, abdominal pain was compared between the two groups. Statistical Package for Social Sciences 23 was utilized to assess data.Results: Ninety (n=90) patients were included in the study and equally segregated into two groups. In Group-A, at 02 hours posts surgery significant pain was present in7(15.55%) patients and in Group-B, in 3(6.66%) patients(p-value:0.18). In Group-A, at 06 hours posts surgery significant pain was present in 5(11.11%) patients and in Group-B in 2(4.44%) patients, (p-value:0.23). In Group-A, at 12 hours posts surgery significant pain was present in2(4.44%) patients and in Group-B in 3(6.66%) patients, (p-value:0.64). In Group-A, at 24 hours posts surgery significant pain was present in 4 (8.88%) patients and in Group-B in 1(2.22%) patient, (p-value:0.16).Conclusion: No significant difference was found between instillation of intraperitoneal Bupivacaine vs Bupivacaine plus Hydrocortisone in terms of post- operative abdominal pain.